Chemical Examination of Abutilon indicum, Tamarix gallicaand Xanthium strumarium - KUMAR, VIPIN; RAWAT, G.S. (Asian Journal of Chemistry, 2010)
Nitrogen, protein, amino acid and vitamin were estimated in three medicinal plants viz., Abutilon indicum, Tamarix gallica and Xanthium strumarium. Xanthium strumarium contains more amount of nitrogen and protein. Abutilon indicum contains vitamin and sugar in comparison to other two plants.